PENGARUH INOVASI DIGITAL TERHADAP KINERJA KEUANGAN PERBANKAN DI INDONESIA - Yogaswari, Dinda Ayu; Diantini, Ni Nyoman Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024DO - 10.24843/EEB.2024.v13.i09.p15, 2024)
The increasingly developing digital era has caused the banking sector to face pressure to adopt new technologies to improve their financial performance and competitiveness. This study aims to determine the effect of digital innovation (mobile banking, internet banking, ATM) on the financial performance of banks in Indonesia. The population of this study was banks listed on the IDX in 2016-2022. The sample was determined using the purposive sampling method, the number of samples was 6 banks. Data collection was carried out using the non-participant observation method. This study uses quantitative data collected from the bank's annual financial reports for 2016-2022. The analysis method used is multiple linear regression analysis. The results of the study show that mobile banking and internet banking have a negative effect, while ATMs have no effect on banking financial performance as measured by ROA. Based on the results of this study, it shows that banks need to be more careful in managing investments in digital technology to optimize financial performance. This study provides practical insights for bank managers in making strategic decisions.